Analisis E Marketing Dalam Meningkatkan Penjualan Pada Aplikasi Belanjo - Muhadan Nurvianto; Erwin Saputra Siregar; Sri Rahma (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
The marketing process in Islamic economics must be implemented correctly, and in accordance with sharia principles. In distributing products, it must be evenly distributed so that all people can enjoy the product. This research is about e-marketing analysis in increasing sales on shopping applications. The purpose of this research is to find out how marketing strategies increase sales on the Belanjo application. This type of research is descriptive qualitative with primary and secondary data types. The data collection technique in this research uses observation, interview and documentation techniques.The research results show the marketing mix strategy implemented by Belanjo to increase sales, including product availability, price, promotion and place. Supporting and inhibiting factors for the marketing mix strategy implemented by Belanjo in increasing sales, including supporting, conducting socialization and collaboration and increasing employee skills and knowledge. obstacles, low consumer buying interest and the marketing area for chips is still limited. Marketing mix strategies viewed from an Islamic Economics Perspective include: Always decorating charity with the intention of worship and sincerity. Transparency, and the goods are halal and not harmful. Carrying out honest distribution methods, not reducing size, standards, quality and scales fraudulently. Being responsible for the goods received. distributed fairly, and not doing things that are prohibited in Islam. Please help, tolerate and give alms. Never neglect worship because of distribution activities. Ikhtikar is prohibited because it will cause price increases. Seek reasonable profits. Widespread distribution of wealth. Social equality.